Analysis of wedding appeals on cigarette packs in China. Issue 6 (9th April 2021) - Trimble, Deana G; Yu, Lingwei; Welding, Kevin; Clegg Smith, Katherine; Cohen, Joanna E
Abstract : Introduction: Exchanging or gifting cigarettes is a common practice in Chinese culture, often occurring during weddings to connote celebrations and happiness. We examined Chinese cigarette packs for wedding terminology and imagery to assess the extent to which packs are marketed for such occasions. Methods: Cigarette packs were collected from Beijing, Guangzhou, Shanghai, Kunming and Chengdu in February 2017 using a systematic protocol designed to capture unique packs. Packs were coded by two independent coders for text and imagery of traditional Chinese wedding symbols, such as double happiness, dragon and phoenix, and other culturally specific phrases and images associated with weddings in China. Results: From the sample of 738 unique cigarette packs, 68 (9.2%) contained either lexical and/or imagery appeals for wedding gifting. Of these 68 packs, 65 contained both lexical and imagery appeals, 1 pack had only a lexical appeal and 2 packs only included an imagery appeal. The most common appeal was 'double happiness' found on 56 packs (82.4%) for both lexical and imagery, followed by 'dragon and phoenix' found lexically on 12 packs (17.6%), and through imagery on 15 packs (22.1%). Conclusions: Chinese tobacco manufacturers take full advantage of the cigarette gifting and sharing culture demonstrated by packs with imagery and terminology specific to weddings. With only a 35% text health warning label, manufacturers have much real estate to make packs attractive for gifting on such occasions. Implementing plain packaging policies may be effective in decreasing gifting attractiveness for cigarette packs.